2017
DOI: 10.1093/mnras/stx1390
|View full text |Cite
|
Sign up to set email alerts
|

A break in the high-redshift stellar mass Tully–Fisher relation

Abstract: We investigate the stellar-mass Tully-Fisher relation (TFR) between the stellar mass and the integrated gas velocity dispersion, quantified by the kinematic estimator S 0.5 measured from strong emission lines in spectra of galaxies at 0 < z < 5. We combine luminosity-selected galaxies ('high-luminosity sample') with galaxies selected in other ways ('low-luminosity sample') to cover a range in stellar mass that spans almost five orders of magnitude: 7.0 ∼ < log M * /M ⊙ ∼ < 11.5. We find that the logarithmic po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 114 publications
1
11
0
Order By: Relevance
“…These data do not suggest that the slope has any dependence on the stellar mass and redshift when using the circular velocity, which is in good agreement with the results from Harrison et al (2017), for example, but in contradiction with Christensen & Hjorth (2017), where they reported a steeper slope for low-mass galaxies. However, this sample is small and more statistics are needed to better look at the variation of the slope with redshift and stellar mass.…”
Section: Tully-fisher Relationsupporting
confidence: 70%
See 1 more Smart Citation
“…These data do not suggest that the slope has any dependence on the stellar mass and redshift when using the circular velocity, which is in good agreement with the results from Harrison et al (2017), for example, but in contradiction with Christensen & Hjorth (2017), where they reported a steeper slope for low-mass galaxies. However, this sample is small and more statistics are needed to better look at the variation of the slope with redshift and stellar mass.…”
Section: Tully-fisher Relationsupporting
confidence: 70%
“…Simons et al (2015) found that the galaxies with log(M /M ) < 9.5 do not follow the Tully-Fisher relation since they show a large scatter at 0.1 < z < 0.375. In addition, Christensen & Hjorth (2017) reported a power-law slope and normalisation independent of the redshift, but also found a break with a steeper slope for low-mass galaxies in their sample at 0 < z < 3 with stellar mass of 7.0<log(M /M )<11.5. In this section, we use KLASS to investigate the redshift and stellar mass evolution of the Tully-Fisher relation to extend these previous studies to low-mass galaxies at 0.6 < z < 2.3.…”
Section: Tully-fisher Relationmentioning
confidence: 93%
“…1. We clearly see a correlation between stellar mass and σHα (see also Christensen & Hjorth 2017). The velocity width of the Hα emission line contains contributions from rotational velocity.…”
Section: Velocity Width As a Proxy Of Stellar Massmentioning
confidence: 57%
“…Several effects could contribute to the observed scatter of the data points relative to that predicted by the various DM halo models. Outflows from galaxies would increase both ∆v90 and σem as the latter also scales with galaxy star-formation rates (Krühler et al 2015;Christensen & Hjorth 2017). Outflows will therefore cause minor increase in the scatter of the ∆v90/σem ratio.…”
Section: Spread Of ∆V90/σem Measurementsmentioning
confidence: 99%